Hookah Smoking in High School Students and Its Determinants in Iran: A Longitudinal Study. (May 2015) - Fakhari, Ali; Mohammadpoorasl, Asghar; Nedjat, Saharnaz; Sharif Hosseini, Mohammad; Fotouhi, Akbar
Hookah smoking has increased worldwide, especially among youth, and has been identified as an emerging threat to public health. The aim of the present study was to estimate the prevalence and transition rates in hookah smoking statuses and predictors of transitions among a representative sample of Iranian high school students. In this longitudinal study, a representative sample ( n = 5197) of students in the northwest of Iran was assessed thrice with a 6-month interval in 2010 and 2011. A self-administered questionnaire was used to measure hookah smoking, demographic characteristics, and personal and environmental factors. In total, the prevalence of hookah use (at least once a month) in this study was 6.0% (95% confidence interval [CI] = 5.1, 6.9). Results indicated that 44.9% (95% CI = 43.0, 46.7) of the students in the sample at least tried hookah smoking. During 1 year, 18.5% and 1.5% of students who have never used hookah before had transitioned to experimenter and regular hookah smoking, respectively, and notably, 7.8% of experimenters had transitioned to regular hookah smoking. Adjusted for other factors, being male, regular cigarette smoking, and positive attitude toward smoking were factors associated with students' transition to hookah smoking status. The incidence rate of hookah smoking in adolescents is notable. The findings identified the co-occurrence of risky behaviors that support programs aimed at reducing or preventing high-risk behaviors simultaneously.